Enabling large-scale screening of Barrett’s esophagus using weakly supervised deep learning in histopathology - Bouzid, Kenza; Sharma, Harshita; Killcoyne, Sarah; Coelho de Castro, Daniel; Schwaighofer, Anton; Ilse, Maximilian; Salvatelli, Valentina; Oktay, Ozan; Murthy, Sumanth; Bordeaux, Lucas; Moore, Luiza; O'Donovan, Maria; et al. (Nature Communications, 2024)
Timely detection of Barrett’s esophagus, the pre-malignant condition of esophageal adenocarcinoma, can improve patient survival rates. The Cytosponge-TFF3 test, a non-endoscopic minimally invasive procedure, has been used for diagnosing intestinal metaplasia in Barrett’s. However, it depends on pathologist’s assessment of two slides stained with H&E and the immunohistochemical biomarker TFF3. This resource-intensive clinical workflow limits large-scale screening in the at-risk population. To improve screening capacity, we propose a deep learning approach for detecting Barrett’s from routinely stained H&E slides. The approach solely relies on diagnostic labels, eliminating the need for expensive localized expert annotations. We train and independently validate our approach on two clinical trial datasets, totaling 1866 patients. We achieve 91.4% and 87.3% AUROCs on discovery and external test datasets for the H&E model, comparable to the TFF3 model. Our proposed semi-automated clinical workflow can reduce pathologists’ workload to 48% without sacrificing diagnostic performance, enabling pathologists to prioritize high risk cases.